2017
DOI: 10.1371/journal.pone.0169385
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Radial Peripapillary Capillaries Using Optical Coherence Tomography Angiography: The Effect of Image Averaging

Abstract: ObjectivesTo assess the effect of image registration and averaging on the visualization and quantification of the radial peripapillary capillary (RPC) network on optical coherence tomography angiography (OCTA).MethodsTwenty-two healthy controls were imaged with a commercial OCTA system (AngioVue, Optovue, Inc.). Ten 10x10° scans of the optic disc were obtained, and the most superficial layer (50-μm slab extending from the inner limiting membrane) was extracted for analysis. Rigid registration was achieved usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(49 citation statements)
references
References 42 publications
2
47
0
Order By: Relevance
“…Multiple B-scan averaging technique is a commonly used method to decrease speckle noise and enhance SD-OCT image quality improving visualization of the fine structures in OCT B-scan (Sander et al 2005;Jorgensen et al 2007;Sakamoto et al 2008;Pappuru et al 2012). Our group and others have shown that averaging can also be applied to enface OCTA images (Maloca et al 2017;Mo et al 2017;Uji et al 2017) and can have an impact on quantitative OCTA metrics. In this study, we evaluate the impact of averaging on image quality, both subjectively and objectively, and propose a level of averaging for optimal image quality.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Multiple B-scan averaging technique is a commonly used method to decrease speckle noise and enhance SD-OCT image quality improving visualization of the fine structures in OCT B-scan (Sander et al 2005;Jorgensen et al 2007;Sakamoto et al 2008;Pappuru et al 2012). Our group and others have shown that averaging can also be applied to enface OCTA images (Maloca et al 2017;Mo et al 2017;Uji et al 2017) and can have an impact on quantitative OCTA metrics. In this study, we evaluate the impact of averaging on image quality, both subjectively and objectively, and propose a level of averaging for optimal image quality.…”
Section: Introductionmentioning
confidence: 97%
“…Even in images with minimum artefact, background noise or small discontinuities in the microcirculation are common. Our group and others have shown that averaging can also be applied to enface OCTA images (Maloca et al 2017;Mo et al 2017;Uji et al 2017) and can have an impact on quantitative OCTA metrics. lower resolution) OCTA images, whether the discontinuity of the vessels is further accentuated due to decrease in decorrelation signals per unit area is obvious.…”
Section: Introductionmentioning
confidence: 99%
“…It has the ability to show both structural and blood flow information. Split‐spectrum amplitude‐decorrelation angiography (SSADA) algorithm (a vital component of OCTA software) helps to quantified the ONH perfusion and retinal vasculature . Published studies describe potential efficacy for OCTA in the evaluation of some ocular diseases such as NAION, glaucoma, multiple sclerosis, diabetic retinopathy, age related macular degeneration (AMD), and so on .…”
Section: Introductionmentioning
confidence: 99%
“…Although glaucoma has been investigated intensely over the years, the elucidation of blood flow and microvasculature in the optic discs of patients with glaucoma remains a challenging research topic. Previous studies of glaucoma often reported fluorescein angiography findings of filling defects (no contrast enhancement) in the intrapapillary capillaries and the disappearance of radial peripapillary capillaries (RPCs) accompanied by an RNFL defect, generating discussions about whether these defects precede or follow visual field loss [ 7 , 8 ]. In addition, reduced intrapapillary, peripapillary, and macular blood flow was recently reported in patients with glaucoma, based mostly on laser speckle flowgraphy (LSFG) findings [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%